Regulation mechanism of sex determination SXL gene treated by RNA interference in/siponostomatioda caligidae/: Магистрын зэрэг горилсон судалгааны ажил. Мэргэжлийн индекс: Е420207 - Тэнүүн Б. (2014)
English